Effect of arginine vasopressin on breathing movements of chronically instrumented fetal lambs - Takefumi Bessho; Yuji Murata; Yuko Ninomiya; Satoshi Ibara; Tatsuo Yamamoto; Yoshiaki Miyake; James G. Tyner (Acta Obstetricia et Gynecologica Scandinavica, 1997)
Background. In hypoxic conditions, fetal breathing movements (FBM) are reportedly inhibited with simultaneous elevation of the plasma level of catecholamines and arginine vasopressin (AVP). Although some kinds of catecholamines are reported to inhibit FBM, the effects of AVP on FBM are still unknown. The present study was undertaken to elucidate whether or not AVP has an inhibitory effect on FBM and electrocortical activities in chronically instrumented fetal lambs. Methods. Arginine vasopressin was injected slowly into the fetal external jugular vein via a catheter over a 30 minute period at an infusion rate of 4.9–10.0 mlU/minute/body. In 15 fetuses (36 estimations) the mean fetal age, mean estimated fetal body weight, and mean infusion dose were 132.4×4.5days, 3.4×0.3kg and 1.7×0.3 mlU/kg/min. Results. The infusion caused a persistent decrease in the fetal heart rate and an increase in the fetal arterial pressure during the 30 minute period. The infusion of AVP resulted in a significant decrease in the incidence of FBM from 36.1 × 14.8% to 12.4×14.9% (p > 0.01). However, there were no significant differences in the incidence of the low voltage fast (LVF) activity before and during infusion of AVP. Conclusion. AVP has an inhibitory effect on FBM. The mechanism of this inhibition was not a direct suppression of the CNS as there was a dissociation between FBM and the electrocortical activity during infusion of AVP.